Overview of Public Knowledge Level About Generic Drugs in Wori Village, Wori District, North Minahasa Regency - Sigar, Meivie Hanna; Lolo, Widya Astuty; Jayanto, Imam (Journal of Literacy and Education, 2025)
The low use of generic drugs in the community is due to the lack of public knowledge about generic drugs. The lack of public knowledge about generic drugs, branded drugs and patent drugs, due to perceptions about generic drugs have low quality, on the other hand, people perceive that patent drugs are quality drugs compared to generic drugs and branded generic drugs. The purpose of this study was to determine the level of community knowledge about generic drugs in Wori Village, Wori District, North Minahasa Regency. This research method is descriptive and uses an instrument (questionnaire), with a cross sectional survey design. The sample in this study were the people of Wori Village who were included in the inclusion criteria as many as 100 samples. The results showed that the level of knowledge of respondents about the definition, benefits, policies, classification, and quality of generic drugs was partly in the good category with a percentage of 54%, 85%, 79%, 95%, 28% respectively. It can be concluded that the level of knowledge about generic drugs in Wori Village is in the good category of 82%.